Transformer l’éducation par les films - Sylvain Wagnon (Revue d’Histoire des Sciences Humaines)
The new education movement emerged at the beginning of the 20th century with a new vision of children, which took into account their needs, and their own interests in what is being taught. Cinema played, and still plays, a large role in the development of these new pedagogies. Our analysis in the first part will focus on the study of cinema within this new educational movement founded by the Belgian psychologist Ovide Decroly (1871-1932), who was, from the start, one of the figures who used cinema most extensively. In the second part, we will analyse Heureux enfants (1955), an unusual film written by Amélie Hamaïde (1888-1970), which is simultaneously in the tradition of the medical films of Ovide Decroly and the documentary films of Henri Storck. In what way does Heureux enfants represent a means of both internationalising Decroly’s pedagogy and maintaining its “orthodoxy”?